Tantangan yang Dihadapi Sekolah Inklusi dalam Menciptakan Pembelajaran setara di SD Muhammadiyah 6 Surabaya: Penelitian - Faniar Sesara Maharani; Apriyanto; Febi Andriyani; Lia Widiastuti; Erna Labudasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to explore the challenges faced by SD Muhammadiyah 6 Surabaya in implementing inclusive education and creating an equal learning environment for both regular and special needs students. The study employs a descriptive qualitative research design to analyze the dynamics of inclusive education, focusing on the interaction between teachers, special needs students, and regular students. Data were collected through in-depth interviews, direct observation, and documentation involving school principals, teachers, and parents of inclusive students. The findings reveal that the main challenges faced by the school include limitations in human resources, lack of teacher readiness, and varied student needs. Despite these challenges, the school has adopted various strategies to create an inclusive learning environment, such as assigning specialized assistant teachers, developing adaptive learning methods, and conducting regular evaluations to monitor student progress. Collaborative efforts between teachers, parents, and school administrators play a crucial role in supporting inclusive education. The study concludes that adaptive teaching strategies, consistent teacher training, and strong collaboration among stakeholders are essential in ensuring the success of inclusive education at SD Muhammadiyah 6 Surabaya.